We found a hat - Klassen, Jon. (Somerville, Mass. : Candlewick Press, 2016)
Two turtles discover a hat that looks good on both of them, but only one can ultimately wear it.
School Library Journal starred, August 2016.
Booklist starred, June 2016.
Horn Book Starred, September 2016.
Pub Weekly, July 2016.
1.3
K-3
Keywords: Hats -- Juvenile fiction; Turtles -- Juvenile fiction; Hats -- Fiction; Turtles -- Fiction; Hats -- Fiction; Turtles -- Fiction; Hats -- Fiction; Lost and found possessions -- Fiction